PENGARUH PERAN SATUAN PENGAWASAN INTERN DAN KOMITE AUDIT TERHADAP TINGKAT PENERAPAN GOOD CORPORATE GOVERNANCE PADA PT PENGEMBANGAN PARIWISATA BALI (PERSERO) /BTDC - Radjagukguk, Marcelinus Sangap Nauli; Ramantha, I Wayan; Mimba, Ni Putu Sri Harta (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME 03. NO.07.TAHUN 2014, 2014)
Research was conducted in PT Pengembangan Pariwisata Bali (Persero) /BTDC . Study aims to know the influence of the Internal Audit’s role and the Audit Committee's role on the implementation level of Good Corporate Governance. Study uses a non-probability sampling type, purposive sampling technique methods, and as much data as 20 respondents. Statistical methods used were multiple regressions. The results of study concludes that Internal Audit’s role and Audit Committee’s role on the implementation level of Good Corporate Governance have a significant and positive effect, the role of Internal Audit against the implementation level of Good Corporate Governance does not have effect, and the role of the Audit Committee on the implementation level of Good Corporate Governance have a significant and positive effect. Keywords: Internal Audit, Audit Committee, Good Corporate Governance, BTDC
Keywords: Internal Audit, Audit Committee, Good Corporate Governance, BTDC